2020
DOI: 10.1039/c9ta11031c
|View full text |Cite
|
Sign up to set email alerts
|

A durable VO2(M)/Zn battery with ultrahigh rate capability enabled by pseudocapacitive proton insertion

Abstract: Reversible hydroxyzinc sulfate hydrate deposition/dissolution in electrochemical process could be observed on cathode surface. Good long term stability retention could also be achieved at high current density of 20 A g−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 59 publications
1
62
1
Order By: Relevance
“…Aqueous rechargeable zinc‐ion batteries (ZIBs) have become one of the most potential electrochemical energy storage devices due to their high energy density, low cost, environmental friendliness, and safety. [ 1–3 ] In terms of energy storage mechanism, compared to monovalent metal ions (such as Li + , Na + ), Zn 2+ allows multiple ionic charges to transport carriers. [ 4,5 ] However, practical application of ZIBs is plagued by the obstacles in cathodes, such as poor cycle stability caused by irreversible lattice distortion and low rate caused by poor conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous rechargeable zinc‐ion batteries (ZIBs) have become one of the most potential electrochemical energy storage devices due to their high energy density, low cost, environmental friendliness, and safety. [ 1–3 ] In terms of energy storage mechanism, compared to monovalent metal ions (such as Li + , Na + ), Zn 2+ allows multiple ionic charges to transport carriers. [ 4,5 ] However, practical application of ZIBs is plagued by the obstacles in cathodes, such as poor cycle stability caused by irreversible lattice distortion and low rate caused by poor conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Zn 2þ intercalation mechanism in Na 2 V 6 O 16 •3H 2 O, a simultaneous H þ and Zn 2þ intercalation was observed in NaV 3 O 8 •1.5H 2 O. [45] Some other types of layered vanadates such as Zn 3 [49] V 2 O 3, [50] VO 2, [51,52] and VS 2 [53] were also reported with Zn 2þ ion storage behaviors in aqueous Zn batteries.…”
Section: Vanadium-based Oxidesmentioning
confidence: 91%
“…Not only VO2 (B) was demonstrated for ZIBs, recently Zhang et al demonstrated VO 2 (M) can be a suitable choice cathode for ZIB. [104] A binder-free cathode was prepared using VO 2 (M) and CNTs which showed 248 mAh g −1 of specific capacity at 2 A g −1 of current, good rate capability, and superior cyclic stability up to 5000 cycles (84.5% retention in specific capacity at 20 A g −1 of current). Authors also studied the energy storage mechanism which was as same as explained by Li et al [101c] However, herein authors showed that VO 2 (M) phase can also be a potential cathode for ZIBs.…”
Section: Multivalent Ion Battery Applicationmentioning
confidence: 99%